THE USE OF HOT POTATOES FOR TEACHING VOCABULARY AT THE ELEVENTH GRADE OF SMA BODHISATTVA - Ezra Setiawan (Bandar Lampung University (UBL), 2016)
Hot Potatoes is an authoring tool which enables teacher to create interactive exercises. The various kinds of exercises are used as web-based learning material. The mixed method research is aimed to find out how the use of Hot Potatoes program facilitates students’ learning process, students’ motivation, and students’ vocabulary achievement. The source of the data is collected through interview, observation, questionnaire and test. The data are analysed both qualitatively and quantitatively. The participants are 16 students at grade eleventh of SMA Bodhisattva Bandar Lampung. Based on the result of analysis, the researcher concludes that the use of Hot Potatoes program can facilitate both students’ learning process and their motivation in learning. Students’ learning process is facilitated from the features of the program which enable them to do exercise with direct feedback, cues of the answer, and automatic evaluation. Students’ motivation is facilitated from the interactivity of the media which makes students interested in learning. In addition, students’ vocabulary achievement is getting improved in which the result shows quite significant difference after doing treatment.